2009
DOI: 10.1371/journal.pone.0007798
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Like Stem Cells Derived from Human Keloid Are Governed by the Inflammatory Niche Driven by IL-17/IL-6 Axis

Abstract: BackgroundAlterations in the stem cell niche are likely to contribute to tumorigenesis; however, the concept of niche promoted benign tumor growth remains to be explored. Here we use keloid, an exuberant fibroproliferative dermal growth unique to human skin, as a model to characterize benign tumor-like stem cells and delineate the role of their “pathological” niche in the development of the benign tumor.Methods and FindingsSubclonal assay, flow cytometric and multipotent differentiation analyses demonstrate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(137 citation statements)
references
References 78 publications
11
125
0
1
Order By: Relevance
“…Reduced stromal IL-6 likely results in decreased epithelial cell damage (38). In addition, IL-6 is active in the tumor stem cell niche (52); reduced secretion may also result in decreased proliferation of dysplastic premalignant cells, thus suggesting a direct effect on tumorigenesis (31,52). Our data are consistent with studies from other laboratories (31,32,53) that have shown that IL-6 plays a key role in the pathogenesis of colitis-associated carcinogenesis.…”
Section: Discussionsupporting
confidence: 85%
“…Reduced stromal IL-6 likely results in decreased epithelial cell damage (38). In addition, IL-6 is active in the tumor stem cell niche (52); reduced secretion may also result in decreased proliferation of dysplastic premalignant cells, thus suggesting a direct effect on tumorigenesis (31,52). Our data are consistent with studies from other laboratories (31,32,53) that have shown that IL-6 plays a key role in the pathogenesis of colitis-associated carcinogenesis.…”
Section: Discussionsupporting
confidence: 85%
“…This finding is important because continuously enlargement of keloid lesion is under responsible of high proliferation rate of KF [3][4][5] and high migration ability to invade surrounding normal tissue. 8 Application 120 uM MC for 72 hours had no significantly different effect in proliferation index and inhibition of cellular migration than 24 hours. Dilution of 120 uM MC into a quarter, oneeighth and so on indicated that significant different (p < 0.05) in KF proliferation and migration was existed on 7.5 uM and below, both 24 hours and 72 hours of administration.…”
Section: Discussionmentioning
confidence: 86%
“…6,7 KF also have a characteristic of mesenchymal stem cells and can migrate to surrounding normal tissues to produce enlargement of fibrous tissues. 8 Moreover, one of various growth factors that have an important role in keloid behavior is transforming growth factor-β (TGF-β). 9 This growth factor can induce Wnt/β-catenin signaling, 10 and over-expression of Wnt is parallel with collagen deposition in both keloid tissues and KF culture.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ABCG2 was the major molecule related to the discovery of the side population, a subpopulation usually less than 2% of the total, and, thus, may become a marker for isolating cancer stem cells [21]. Recently, keloid stem cells have been discovered and were proposed to contribute to keloid pathogenesis [8,9]. Therefore, the relationship between membrane transporters and keloid stem cells, as well as their roles in keloid pathogenesis, could be an interesting area for further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the discovery of cancer stem cells was based on the finding of a "side population" that does not stain strongly with Hoechst 33342 because of the activity of the membrane transporter ABCG2 [6,7]. Recently, stem cells have been discovered in keloid tissue and are believed to play a key role in keloid development, pathogenesis, and recurrence [8,9].…”
Section: Introductionmentioning
confidence: 99%